2022
DOI: 10.1186/s43043-022-00112-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection control protocol and acceptance in an ART in vitro fertilization hospital

Abstract: Purpose In Tokyo, where the highest coronavirus disease 2019 (COVID-19) infection rates have been reported nationally, we introduced and performed polymerase chain reaction (PCR) testing on the patients prior to them coming for oocyte retrieval (OR) or embryo transfer (ET) procedures. In addition, we recommended that patients self-inject ovarian stimulation drugs to reduce the number of hospital visits required. We aimed to assess the patient acceptance of these measures and the change of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The hope is that the reduced risk of exposure could potentially lower the number and frequency of egg retrieval appointment cancellations and treatment delays due to COVID-19. A retrospective study at our institution showed no significant differences in the pregnancy rate or number of egg retrievals based on home injections compared to in-hospital methods, such as human menopausal gonadotrophin (hMG), and is expected to become a mainstream method for ovarian stimulation in the future [18].…”
Section: Discussion / обсуждениеmentioning
confidence: 96%
“…The hope is that the reduced risk of exposure could potentially lower the number and frequency of egg retrieval appointment cancellations and treatment delays due to COVID-19. A retrospective study at our institution showed no significant differences in the pregnancy rate or number of egg retrievals based on home injections compared to in-hospital methods, such as human menopausal gonadotrophin (hMG), and is expected to become a mainstream method for ovarian stimulation in the future [18].…”
Section: Discussion / обсуждениеmentioning
confidence: 96%